Kewenangan Jabatan Notaris dalam Keadaan Terbatas: Studi Terhadap Penahanan Kota dan Penahanan Rumah - Livia Kusumadiani Putri; Ariawan Gunadi (Jurnal Hukum Lex Generalis, 2025)
This research discusses the authority to perform the duties of a Notary who is undergoing house arrest or city arrest, with a case study of the Medan High Court Decision Number 9/PID.SUS-TPK/2023/PT MDN. The main issues raised are the legal status, authority, and implications of detention on the performance of a Notary's duties according to the UUJN and the professional code of ethics. The analysis of norms and decisions shows a lack of clarity in regulations, but it was found that detention can limit the authority of a Notary. In conclusion, stricter regulations are needed regarding the performance of a Notary's duties while under house arrest or city detention to ensure legal certainty and justice.